Investitionen in die Integration der Flüchtlinge lohnen sich - Stefan Bach; Herbert Brücker; Peter Haan; Agnese Romiti; Kristina van Deuverden; Enzo Weber (DIW Wochenbericht, 2017)
Die Zuwanderung von Flüchtlingen verursacht zunächst erhebliche fiskalische Kosten. Mit zunehmender Integration in den Arbeitsmarkt verringern sich die laufenden Kosten und es entstehen zusätzliche Einnahmen für die öffentlichen Haushalte. Vor diesem Hintergrund haben IAB und DIW Berlin gemeinsam in einem vom Bundesministerium für Arbeit und Soziales finanzierten Forschungsprojekt untersucht, wie sich Investitionen in die Arbeitsmarktintegration der 2015 zugewanderten Flüchtlinge gesamtwirtschaftlich und fiskalisch auswirken können. Es zeigt sich, dass Investitionen in Sprachkompetenz und Bildungsabschlüsse der Flüchtlinge langfristig hohe Renditen erwarten lassen. – – The initial fiscal costs associated with refugee integration are quite high - but as more and more refugees join the labor force, a reduction in ongoing welfare costs and an increase in government revenue will result. Against this background, the Institute for Employment Research (IAB) in Nuremberg and DIW Berlin conducted a joint investigation (funded by the German Federal Ministry of Labor and Social Affairs) on the overall economic and fiscal impacts of investing in the labor market integration of the refugees who arrived in Germany in 2015. The study shows that investing in refugees' language skills and educational qualifications promise high returns.
Keywords: F22; I21; H52; 330; refugees; migration; labor market integration; budget impact